Pengaruh Kepemilikan Manajerial, Struktur Modal, Ukuran Perusahaan, dan Agency Cost sebagai Variabel Intervening terhadap Kinerja Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI - Immanuela, Intan (Widya Warta, 2014)
The purpose of this research is to find empirical evidence of the influence of managerial ownership, equity structure, size, and agency cost as intervening variables toward the performance of the companies listed in BEI (Indonesia Stock Exchange). The data of study are the financial reports of manufacture companies listed in BEI in the period 2009 – 2011. They were collected from www.idx.co.id. and Indonesian Capital Market Directory (ICMD). To get the sample, the study made use of purpose sampling method based on the criteria as follows: 1) the manufacture companies were listed in BEI in the period 2009 – 2011, 2) the companies issued their financial reports in the period 2009 – 2011 conforming to the complete data needed in this research. Due to the research criteria, the companies obtained as the sample are 24 in number. The data were analyzed using multiple regression analysis method. The results of the study indicated that 1) managerial ownership, equity structure, and size did not influence the agency cost both directly and indirectly, 2) managerial ownership and size did not influence the performance of the companies through the agency cost both directly and indirectly. There were, however, some significant influences between the equity structure and the performance of the companies.